2008
DOI: 10.1080/00140130802248092
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a comprehensive slip, trip and fall prevention programme for hospital employees

Abstract: In 2007, the Bureau of Labor Statistics reported that the incidence rate of lost workday injuries from slips, trips and falls (STFs) on the same level in hospitals was 35.2 per 10,000 full-time equivalents (FTE), which was 75% greater than the average rate for all other private industries combined (20.2 per 10,000 FTEs). The objectives of this 10-year (1996-2005) longitudinal study were to: 1) describe occupational STF injury events in hospitals; 2) evaluate the effectiveness of a comprehensive programme for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(124 citation statements)
references
References 22 publications
3
121
0
Order By: Relevance
“…Injury and injury-related musculoskeletal conditions were the leading cause of outpatient visits and the fourth leading cause of hospitalizations. The present findings are consistent with previous reports showing the relative importance of injuries as a cause of morbidity and mortality among all active duty Army personnel Marshall et al, 2014) as well as civilian hospital personnel (Bell et al, 2008;Boden et al, 2012;Dawson et al, 2007;Jabbour et al, 2015;Oude Hengel et al, 2011;Perhats et al, 2012;Rodriguez-Acosta et al, 2009). …”
Section: Medcom Injury Medical Encounterssupporting
confidence: 83%
See 1 more Smart Citation
“…Injury and injury-related musculoskeletal conditions were the leading cause of outpatient visits and the fourth leading cause of hospitalizations. The present findings are consistent with previous reports showing the relative importance of injuries as a cause of morbidity and mortality among all active duty Army personnel Marshall et al, 2014) as well as civilian hospital personnel (Bell et al, 2008;Boden et al, 2012;Dawson et al, 2007;Jabbour et al, 2015;Oude Hengel et al, 2011;Perhats et al, 2012;Rodriguez-Acosta et al, 2009). …”
Section: Medcom Injury Medical Encounterssupporting
confidence: 83%
“…Therefore, the mechanisms of injury among active duty MEDCOM personnel may differ from those of civilian hospital personnel. Civilian studies of hospital employees have identified the most common mechanisms of injury to be overexertion, lifting, slips, trips, and falls, and being struck by or against an object (Bell et al, 2008;Boden et al, 2012;Jabbour et al, 2015;Perhats et al, 2012;Pompeii et al, 2008;Rodriguez-Acosta et al, 2009;Scott and Newman, 2013). Studies have also indicated that some of the injuries among civilian hospital personnel are due to patient moving and lifting (Bell et al, 2008;Perhats et al, 2012;Pompeii et al, 2008).…”
Section: Medcom Injury Causes and Typesmentioning
confidence: 99%
“…Two endoscopy personnel working on hospital grounds suffered Type-II accidents during patient rounds (Table 1, 15,16). Both were male gastroenterologists.…”
Section: Resultsmentioning
confidence: 99%
“…Many accidents newly described in the endoscopy suite have been previously reported in other hospital/industrial environments, including: slip and fall on wet floors covered with regular (not slip-resistant) floor tiles [15,16], nurse falls from breaking falls of unsteady patients [17], back injury from turning severely obese patients on stretchers [18], and trip and falls over pathway obstacles, including improperly parked wheelchairs [19]. Nurses are at risk of injury from breaking a patient's fall, when patients are unsteady from residual effects of anesthesia after procedures.…”
Section: Discussionmentioning
confidence: 96%
“…For example, changes to injury narrative trends were used to measure slip and fall injuries in hospitals due to a broad-scale intervention (Bell, Collins et al, 2008). Not only was the analysis able to determine the overall effectiveness of the program, but also the effect the program was having on different sources of falls, allowing future interventions to be targeted accordingly.…”
mentioning
confidence: 99%